Optimizing the physical activity intervention for older adults with mild cognitive impairment: a factorial randomized trial - Shao, Zhanfang; Huang, Jundan; Feng, Hui; Hu, Mingyue (Frontiers in Sports and Active Living, 2024)
Background: Physical activity (PA) intervention is among the most effective interventions to promote cognitive function for older adults with mild cognitive impairment (MCI). However, the level of PA is still low. Based on the two core interventions (X-CircuiT and health education), this study aimed to examine the effect of three implementation strategies (role modeling, goal-setting, and reminding) on the PA level using the Multiphase Optimization Strategy (MOST) among older adults with MCI.Methods: Participants were randomized to one of eight conditions in a factorial design involving three factors with two levels: i) role modeling (on vs off); ii) goal-setting (on vs off); and iii) reminding (on vs off). The primary outcome was PA level at 12-week.The secondary outcomes were cognitive function, self-efficacy, and cost-effectiveness at 12-week. The intention-to-treat (ITT) was performed as the main analysis and the per-protocol (PP) analysis as the sensitivity analysis.Results: A total of 107 participants were included and they were randomly assigned into three groups with different implementation strategies. The results of the multivariate regression analysis showed that three implementation strategies of reminding (B = 0.31, p < 0.01), role modeling (B = 0.21, p < 0.01), and goal-setting (B = 0.19, p < 0.01) could significantly improve PA level. Role modeling (B = 0.68, p = 0.03) could significantly improve cognitive function. There were no significant interactions among the three implementation strategies. Role modeling was the most cost-effective strategy, costing 93.41 RMB for one unit of PA.Conclusions: Role modeling was likely to be the best implementation strategy. The value-based and cost-effective PA intervention package could include the core intervention (X-CircuiT and health education) and implementation strategy (role modeling).The study was retrospectively registered on 30 June 2022 (ChiCTR2200061693).